2022
DOI: 10.1038/s43705-022-00094-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring rhizo-microbiome transplants as a tool for protective plant-microbiome manipulation

Abstract: The development of strategies for effectively manipulating and engineering beneficial plant-associated microbiomes is a major challenge in microbial ecology. In this sense, the efficacy and potential implications of rhizosphere microbiome transplant (RMT) in plant disease management have only scarcely been explored in the literature. Here, we initially investigated potential differences in rhizosphere microbiomes of 12 Solanaceae eggplant varieties and accessed their level of resistance promoted against bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 86 publications
0
44
0
Order By: Relevance
“…Bacteroidetes is a core microbial taxon in the plant-associated microbiome and are highly enriched in some plants [64]. Several microbial species belonging to Bacteroidetes, for example Flavobacterium, Chryseobacterium and Pedobacter have been reported to inhibit microbial pathogens [29,65,66]. Flavobacterium species that were inoculated to cucumber seedlings suppressed Fusarium [67].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteroidetes is a core microbial taxon in the plant-associated microbiome and are highly enriched in some plants [64]. Several microbial species belonging to Bacteroidetes, for example Flavobacterium, Chryseobacterium and Pedobacter have been reported to inhibit microbial pathogens [29,65,66]. Flavobacterium species that were inoculated to cucumber seedlings suppressed Fusarium [67].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, microbial consortia from host plants may have a high abundance of bene cial microbes with a high functional redundancy, including antagonists that suppress pathogens [26][27][28]. Jiang et al, [29] reported the protective potential of rhizosphere microbiome consortia against the bacterial wilt pathogen Ralstonia solanacearum. Overall, a successful transfer of "primed" or induced plant-associated microbial consortia could confer both growth stimulating traits as well as enduring resistance against pathogens [28, 30,31].…”
Section: Introductionmentioning
confidence: 99%
“…At least three phases can be used for control: (i) germination of the resting spores and/or secondary spores, which initiate (ii) primary infection of the root hairs and secondary infection of the root cortex; (iii) antagonism/competition against the developing pathogen within the host root tissue. In addition, resistance induction in host plants and changes in microbial communities in the rhizosphere soil could be biological control options [ 60 ].…”
Section: Clubroot Control Using Beneficial Microorganismsmentioning
confidence: 99%
“…AMF biofertilizers alleviated replanting diseases of American ginseng by reducing deleterious Fusarium oxysporum , F. solani and Candidatus Solibacter [ 235 ]. Furthermore, Jiang et al [ 317 ] revealed that the rhizosphere edaphon of resistant varieties could recruit distinct bacterial taxa associated with disease suppression. It was advocated that microbial transplantation from resistant donors should be promising to modulate soil microecology and plant health.…”
Section: Function Of Soil Microorganisms In Growth Promotion and Qual...mentioning
confidence: 99%